KEENGGANAN WAJIB PAJAK UMKM UNTUK MENGIKUTI TAX AMNESTY - NOOR RHAMANDA, ANUGRAH; PRASTIWI, DEWI (Jurnal Akuntansi AKUNESA, 2017)
Tax amnesty is the elimination of tax payable but will not be subject to administrative sanctions and criminal sanctions if the revealed treasures and paying ransom. A tax amnesty aimed at restoring property taxpayers inside or outside the country and to improve the countrys acceptance of the tax sector. This research aimed to identify the factors that influence tax payer SMEs reluctance to participate the tax amnesty 2016. The methods used in this research is qualitative method with descriptive approach. Data collection techniques in the study using interview techniques with the SME?s taxpayers who do not follow the tax amnesty as the subject of the tax. Techniques for testing the validity of the data in this study using the technique of triangulation. The results of the analysis showed that the factor of the taxpayers reluctance toward a tax amnesty is lack of understanding and curiosity, experience, level of service that is less effective, and the influence of the environment of SME?s.